Conditional Cripto overexpression in satellite cells promotes myogenic commitment and enhances early regeneration - Prezioso, Carolina; Iaconis, Salvatore; Andolfi, Gennaro; Zentilin, Lorena; Iavarone, Francescopaolo; Guardiola, Ombretta; Minchiotti, Gabriella (Frontiers in Cell and Developmental Biology, 2015)
Skeletal muscle regeneration mainly depends on satellite cells, a population of resident muscle stem cells. Despite extensive studies, knowledge of the molecular mechanisms underlying the early events associated with satellite cell activation and myogenic commitment in muscle regeneration remains still incomplete. Cripto is a novel regulator of postnatal skeletal muscle regeneration and a promising target for future therapy. Indeed, Cripto is expressed both in myogenic and inflammatory cells in skeletal muscle after acute injury and it is required in the satellite cell compartment to achieve effective muscle regeneration. A critical requirement to further explore the in vivo cellular contribution of Cripto in regulating skeletal muscle regeneration is the possibility to overexpress Cripto in its endogenous configuration and in a cell and time-specific manner. Here we report the generation and the functional characterization of a novel mouse model for conditional expression of Cripto, i.e., the Tg:DsRedloxP/loxPCripto-eGFP mice. Moreover, by using a satellite cell specific Cre-driver line we investigated the biological effect of Cripto overexpression in vivo, and provided evidence that overexpression of Cripto in the adult satellite cell compartment promotes myogenic commitment and differentiation, and enhances early regeneration in a mouse model of acute injury.